Sulforaphane Exerts Beneficial Immunomodulatory Effects on Liver Tissue via a Nrf2 Pathway-Related Mechanism in a Murine Model of Hemorrhagic Shock and Resuscitation - Liang, Weiqiang; Greven, Johannes; Qin, Kang; Fragoulis, Athanassios; Horst, Klemens; Bläsius, Felix; Wruck, Christoph; Pufe, Thomas; Kobbe, Philipp; Hildebrand, Frank; Lichte, Philipp (Frontiers in Immunology, 2022)
Our research explores the immunomodulatory effects of sulforaphane (SFN), a well-known nuclear factor erythroid 2-related factor 2 (Nrf2) pathway agonist, on the sterile inflammation of and ischemia-reperfusion injuries to the liver after hemorrhagic shock (HS) followed by resuscitation (R). Male C57/BL6 wild-type and transgenic ARE-luc mice were exposed to mean arterial pressure-controlled HS. Fluid resuscitation was performed after 90 min of HS, and SFN was administrated intraperitoneally after that. The animals were sacrificed at 6 h, 24 h, and 72 h after resuscitation, and their livers were extracted to perform H&E staining and myeloperoxidase (MPO) activity analysis. The Kupffer cells were isolated for cytokine profile measurements and Nrf2 immunofluorescence staining. Further, the ARE-luc mice were used to assess hepatic Nrf2 activity in vivo. We identified that SFN-activated Kupffer cells’ Nrf2 pathway and modulated its cytokine expression, including TNF-α, MCP-1, KC/CXCL1, IL-6, and IL-10. Furthermore, SFN mitigated liver ischemia-reperfusion injury, as evidenced by the downregulation of the Suzuki score and the enhanced hepatic Nrf2 activity. The in vivo SFN treatment decreased neutrophils infiltration, as shown by the decreased MPO levels. Our study shows that SFN can decrease HS/R-induced hepatic ischemia-reperfusion injury and modulate the activity of Kupffer cells via an Nrf2-dependent pathway.